Every day activities and gait quality in patients after total hip arthroplasty - Borowicz, Barbara; Cielicka, Małgorzata; Nadulska, Anna; Teter, Mariusz; Dec-Szlichtyng, Mariola (Nursing in the 21st Century, 2012)
EVERY DAY ACTIVITIES AND GAIT QUALITY IN PATIENTS AFTER TOTAL HIP ARTHROPLASTYAim. The aim of this study was evaluation of daily living activity and of gait in patients after total hip arthroplasty.Material and methods.The study comprised 100 persons after total hip replacement surgery. The evaluation of effectiveness of operation was carried out on the basis of the inquiry prepared by the authors.Results. Before operation as much as 65% of patients  each day felt hip pain. This pain made it  impossible to perform many of daily activities. About 75% of patients had difficulties with such activities as: walking, going upstairs and downstairs, sitting, getting up from the bed, coming in and out the car, washing oneself in the bath, putting on the socks and the shoes and lacing the shoes.After operation in 61% patients the pain made it possible to perform their work and the majority of above mentioned difficulties of daily living was decreased. Before arthroplasty majority of patients walked with stick and limped markedly.Due to the operation percentage of persons, who walked without orthopedic equipment was significant increased.Conclusions. According to majority of patients the hip arthroplasty improved their motor activity . Increased self- independence in activities of daily living and in gait was noticed.